Tersilochinae (Hymenoptera: Ichneumonidae) from New Zealand. Part 2. Review of genera Kiwi gen. nov. and Zealochus Khalaim - Khalaim, Andrey I.; Ward, Darren F. (Zootaxa, 2019)
In the second paper on New Zealand Tersilochinae (Ichneumonidae) we review two endemic New Zealand genera, Kiwi gen. nov. (eight species) and Zealochus Khalaim (three species). Nine species are described as new to science: Kiwi barrattae sp. nov., K. canterberus sp. nov., K. earlyi sp. nov., K. gronous sp. nov., K. oreteus sp. nov., K. ruzelus sp. nov., K. waitakerus sp. nov., Zealochus abominosus sp. nov. and Z. stepheni sp. nov. Zealochus gauldi Khalaim is transferred to Kiwi (comb. nov.). Identification keys to species of Kiwi and Zealochus occurring in New Zealand are provided.